Effect of modified di- and trisaccharides on hyaluronidase activity assessed by capillary electrophoresis-based enzymatic assay. (1st March 2019) - Fayad, Syntia; Ayela, Benjamin; Chat, Coralie; Morin, Philippe; Lopin-Bon, Chrystel; Nehmé, Reine
Abstract: The activity of eukaryote hydrolase-type of hyaluronidases was studied using a miniaturized capillary electrophoresis (CE) assay developed in our laboratory. Few nanoliters of reagents are sufficient and no labeling is required for this assay. The effect of natural and original synthetic effectors of hyaluronidase was evaluated. These di- and trisaccharides from linkage region of proteoglycans were synthesized in 30–40 steps from monomeric units using classical protection, deprotection, glycosylation and deoxygenation reactions. The influence of the chain length (di/trisaccharide), the modification type (methoxy/deoxy) and its position (2/4/6) was studied. The inhibition and/or activation percentages were determined at two concentrations of effectors; 0.2 mM and 2 mM. The half maximal effective concentration (EC50 ) values were evaluated (n = 2) for the most effective inhibitors (∼1 mM) and activators (∼0.2 mM). Results showed that hyaluronidase was mostly inhibited in a concentration-dependent fashion by a deoxy modification and activated by a methoxy modification. Trisaccharides were found to be more effective on hyaluronidase activity than disaccharides. Position 4 was found to be more favorable for hyaluronidase activity than position 6 and the activity in position 2 was negligible. For a better understanding of the enzyme function mode, the inhibition constant (Ki ) was also evaluated by CE (Ki ∼ 2 mM). These results are of great interest especially as few activators of hyaluronidase are presented in the literature. Graphical abstract: Image 1 Highlights: A generic capillary electrophoresis assay for studying hyaluronidase activity. A small library of di- and trisaccharides screened for hyaluronidase modulation. Deoxy modification inhibits hyaluronidase while methoxy modification activates it. Hyaluronidase modulated mainly by trisaccharides and modification on position 4. IC50 and AC50 of most potent compounds toward hyaluronidase evaluated by CE.